Answer:
x = -8 and x = 4
Step-by-step explanation:
given
f(x) = (x+8) (x - 4)
recall that at any point on the x-axis, y = 0 [i.e f(x) = 0]
hence to find where the graph crosses the x-axis, we simply substitue f(x) = 0 into the equation and solve for x
f(x) = (x+8) (x - 4)
0 = (x+8) (x - 4)
Hence
either,
(x+8) = 0 ----> x = -8 (first crossing point)
or
(x-4) = 0 ------> x = 4 (second crossing point)
Hence the graph crosses the x-axis at x = -8 and x = 4
I think it’s 4.308 when u multiply
The simplified version of this x-2z
Step-by-step explanation:
You need to start by combining like terms. You can start with the terms that have the variable x in them. By combining those terms, the equation becomes x+3y-z-3y-z.
From here, you can combine the terms 3y and -3y, which bring the equation to x-z-z.
From here, combine the terms with the variable z. This would bring the equation down too x-2z, your final answer.
Answer:
44 and 22
Step-by-step explanation: